PENANGGUHAN PENAHANAN TERHADAP TAHANAN PEREMPUAN YANG BERSTATUS IBU YANG MEMILIKI BALITA - Putri, Nurul Izzah Alia; Erdianto, Erdianto; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Suspension of detention is the right of suspects or detainees, which isregulated in Article 31 of the Criminal Procedure Code. This suspension ofdetention gives an agency the freedom to provide reasons for granting orrefusing a suspension of detention, meaning that in this case it is the fullauthority of the competent agency. However, in reality the suspension ofdetention here is still not optimal, both in its arrangement and implementation.This can be seen from the discovery of several rejections of suspension ofdetention, especially in several cases where the suspect was a mother with atoddler. This thesis research aims to: first, to describe the regulation andimplementation of suspension of detention for female detainees who are motherswith toddlers in the Indonesian criminal courts. Second, to describe theappropriate rules regarding the suspension of detention for female detaineeswho are mothers of toddlers from a substantive justice perspective.This type of research can be classified as normative legal research,because this research is carried out by examining library materials or secondarydata. In this research, the data sources used are primary data, secondary dataand tertiary data. The data collection technique in this research is the libraryresearch method.From the results of the research carried out, it can be concluded that, inrelation to this, the implementation obtained from several cases involving femaledetainees who have the status of mothers, shows that the existing regulationsstill have weaknesses or there is no certainty about the regulations in this case,so that it can It is said that implementation has not gone well. Therefore, it isnecessary to reform in the form of a special law regarding the rules forsuspending the detention of women detainees who are mothers who havetoddlers in more detail, by not only focusing on procedural matters, but alsoconsidering substantively for the sake of realizing legal justice and legalcertainty. regarding suspension of detention, especially in relation to femaledetainees who are mothers of toddlers.